ChemInform Abstract: Supramolecular Chemistry of Fullerenes on Solid Surfaces. Issue 31 (11th July 2013) - Otero, Roberto; Gallego, Jose Maria; Martin, Nazario; Miranda, Rodolfo
Abstract Review: 72 refs.